Asas Monogami Dalam Hukum Perkawinan Di Indonesia - Sari, Vincensia Esti Purnama (LAW REVIEW, 2006)
The understanding of marriage according to Law Number I Year 1974 is a union in every respect between a man and a woman as husband and wife to create a happy and everlasting family based on Cod. A marriage in Indonesia is legal if it is done based on the Religion or individual belief. Marriage is based on monogamy principle that under a marriage, a man may have only one wife and a woman may have only one husband. Â The implementation of monogamy principle in Indonesia has a deviation known as polygamy. Law Number 1 Year 1974 allows polygamy for a man who wants to have more than one wife with the condition that his religion allows him to do it as long as his wife/wives agree with, and which is written in an agreement.